2021
DOI: 10.3390/jmse9101092
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Analysis of the Causes of Intensive Harmful Algal Bloom in Kamchatka Based on Satellite Data

Abstract: In this paper, the causes of the anomalous harmful algal bloom which occurred in the fall of 2020 in Kamchatka have been detected and analyzed using a long-term time series of heterogeneous satellite and simulated data with respect to the sea surface height (HYCOM) and temperature (NOAA OISST), chlorophyll-a concentration (MODIS Ocean Color SMI), slick parameters (SENTINEL-1A/B), and suspended matter characteristics (SENTINEL-2A/B, C2RCC algorithm). It has been found that the harmful algal bloom was preceded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…Moreover, our particle-tracking simulations revealed that the Pacific Ocean to the east of the Kamchatka Peninsula could be the other potential source. This possibility is consistent with the outbreaks of K. selliformis in September-October 2020 [18,19]. These observations lead to the hypothesis that different algal species may have been separately transported from the three potential source areas and contributed simultaneously to the occurrence of the HABs off the southeast coast of Hokkaido in late summer of 2021.…”
Section: Possible Linkages From Algal Transport To Outbreaksupporting
confidence: 68%
See 4 more Smart Citations
“…Moreover, our particle-tracking simulations revealed that the Pacific Ocean to the east of the Kamchatka Peninsula could be the other potential source. This possibility is consistent with the outbreaks of K. selliformis in September-October 2020 [18,19]. These observations lead to the hypothesis that different algal species may have been separately transported from the three potential source areas and contributed simultaneously to the occurrence of the HABs off the southeast coast of Hokkaido in late summer of 2021.…”
Section: Possible Linkages From Algal Transport To Outbreaksupporting
confidence: 68%
“…In the second step, 87,616 particles were initially set at each of three depths (1, 5, and 10 m) below the sea surface east of the Kamchatka Peninsula and tracked forward in time for 360 days. Initial conditions of the particles were updated at intervals of five days from 30 September to 20 October 2020, which corresponded to the period of occurrence of the HABs off the east coast of the Kamchatka Peninsula [18].…”
Section: Particle-tracking Simulationmentioning
confidence: 99%
See 3 more Smart Citations